Ethnic self-identification of first-generation immigrants - Laura Zimmermann; Klaus F. Zimmermann; Amelie F. Constant (Institute for the Study of Labor (IZA), 2006)
This paper uses the concept of ethnic self-identification of immigrants in a two-dimensional framework. It acknowledges the fact that attachments to the home and the host country are not necessarily mutually exclusive. There are three possible paths of adjustment from separation at entry, namely the transitions to assimilation, integration and marginalization. We analyze the determinants of ethnic self-identification in this process using samples of first-generation immigrants for males and females separately, and controlling for pre- and post-migration characteristics. We find strong gender differences and the unimportance of a wide range of pre-migration characteristics like religion and education at home.
urn:nbn:de:101:1-2008042951
Keywords: 330